An exploratory study on online misinformation appraisal behavior of undergraduate students from the University of the Philippines Diliman - Espina, Patricia Louise C. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Information has always been a vital part of everyday life, starting from the process of gaining and sharing it through word of mouth to printed sources and at present through online platforms. Pairing the value of information with the continuous development of technology and popularity of the internet, information nowadays has become more susceptible to misinformation. In line with this exposure are various online information seeking behaviors of users.